Content Validity Of The Ethiopian University Entrance English Language Examinations Of 2011/12-2013/14 - Yilma Legesse (My University, 2015)
The purpose of this study was to assess whether the Ethiopian University Entrance English Examinations of 2011/2- 2013/4 administered by the National Educational Assessment and Examinations Agency fairly represent the content coverage and adequate sampling of the objectives stated in the syllabus. To attain this, Mixed Method Approach was used. The qualitative methods was used to justify, clarify and interpret the data collected through semi structured interview and questionnaire while the quantitative method was used to show the outcomes of Pearson’s chisquare test of independence and Cramer’s coefficient of association. The raw data for the study was collected using syllabus and SAT content analysis, and semi structured interview with 2 testing experts to cross check the data obtained from the document analysis. Purposive sampling and availability techniques were used to select the sources of data and analysts of this study respectively. The content validity of the contents of the syllabus of grade 11 and 12; and EUEE (SAT) were analyzed using the standards of measuring content validity. The collected data were analyzed by using Chi-square Test of Independence and Cramer’s Coefficient of contingency to test the goodness-of-fit and strength of association between the contents of the syllabus and SATs respectively. Conclusion was made both testing the null and alternative hypothesis. Finally, the data obtained from the content analysis was triangulated with that of the semi structured interview